(3GdLGeYI GdLRGFQjI(B: (3aj Xd GdGJLGgGJ GdMOjKI ddJYdje GdYGdjs - (3ThJQj(B, (3CeGds; (3HhfbjH, CMeOs; (3TjNI, djdis ((3GdLRGFQs (3OGQ GdHGMK ddWHGYI hGdfTQ hGdJhRjYs, 2021)
(3GdSjfGQjhgGJ GdeMJedI deSJbHd GdJYdje GdYGdj HGdLRGFQhGTcGdjI GdJYGed eY JcfhdhLjG GdeYdheGJ hGdGJUGd, hGdJYdje GdYGdj aj GdLRGFQ hefWb GdYdGL HGdUOeI, hCNjQG GdGOGQI GdMOjKI ddCOGA aj eDSSGJ GdJYdje GdYGdjaj YUQ GdeYQaI, hGdJNWjW GdGSJQGJjLj aj GdLGeYGJ Hjf GdMJejI hGdJbdjO(B.s
Keywords: (3GdJYdje GdYGdjs; (3GdLGeYI(B: (3GdLRGFQs